The 2020 Arctic ozone depletion and signs of its effect on the ozone column at lower latitudes - Petkov, Boyan; Vitale, Vito; Di Carlo, Piero; Mazzola, Mauro; Lupi, Angelo; Diémoz, Henri; Fountoulakis, Ilias; Drofa, Oxana; Mastrangelo, Daniele; Casale, Giuseppe Rocco; Siani, Anna Maria (Bulletin of Atmospheric Science and Technology, 2021)
The present study discusses the effect of the ozone depletion that occurred over the Arctic in 2020 on the ozone column in central and southern Europe by analysing a data set obtained from ground-based measurements at six stations placed from 79 to 42°N. Over the northernmost site (Ny-Ålesund), the ozone column decreased by about 45% compared to the climatological average at the beginning of April, and its values returned to the normal levels at the end of the month. Southwards, the anomaly gradually reduced to nearly 15% at 42°N (Rome) and the ozone minimum was detected with a delay from about 6 days at 65°N to 20 days at 42°N. At the same time, the evolution of the ozone column at the considered stations placed below the polar circle corresponded to that observed at NyÅlesund, but at 42°–46°N, the ozone column turned back to the typical values at the end of May. This similarity in the ozone evolutional patterns at different latitudes and the gradually increasing delay of the minimum occurrences towards the south allows the assumption that the ozone columns at lower latitudes were affected by the phenomenon in the Arctic. The ozone decrease observed at Aosta (46°N) combined with predominantly cloud-free conditions resulted in about an 18% increase in the erythemally weighted solar ultraviolet irradiance reaching the Earth’s surface in May.